Breve introdución á Terminoloxía. Exemplo de elaboración dun traballo terminolóxico en galego - Montes García, Laura (Madrygal. Revista de Estudios Gallegos, 2008)
This article is divided into two distinct parts. One area that is a little closer to the theory termonologic. To begin this review by the different papers and people from s. XVI until today. After trying to define and delimit the discipline to which we refer to as its object of estudy. The second part consists of a description of the steps we take to develop a small terminology work on the language of ecology. The terms were extracted from the section “O noso planeta” into the magazine O correo da Unesco.